2018
DOI: 10.15503/jecs20181.39.49
|View full text |Cite
|
Sign up to set email alerts
|

The development and implementation of ideas of lifelong learning in Europe at the dawn of the 21st century

Abstract: Aim. The aim of article is present the changing of idea of lifelong learning. The article focuses on the idea of lifelong learning. The first part shows the essence of lifelong learning. An attempt has been made to organise concepts like: lifelong learning, lifelong training, continuing education and permanent education, as well as education and adult education, to consequently educe the idea of lifelong learning from the concept of continuing education. Methods. It’s used  the literature analysis becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Molteni et al [32] established that personalities with lower education significantly use ICT tools rarely for various purposes in both developing and developed countries. Marcinkiewicz-Wilk and Jurczyk-Romanowska [33] showed that computer competence correlated with computer use among university lecturers in the United States of America. ey, therefore, concluded that computing confidence greatly influenced university preparedness on ICT implementation.…”
Section: Teachers' Competenciesmentioning
confidence: 99%
“…Molteni et al [32] established that personalities with lower education significantly use ICT tools rarely for various purposes in both developing and developed countries. Marcinkiewicz-Wilk and Jurczyk-Romanowska [33] showed that computer competence correlated with computer use among university lecturers in the United States of America. ey, therefore, concluded that computing confidence greatly influenced university preparedness on ICT implementation.…”
Section: Teachers' Competenciesmentioning
confidence: 99%